2019
DOI: 10.1093/conphys/coz009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carotenoid class and dose on the larval growth and development of the critically endangered southern corroboree frog

Abstract: This study shows that dietary β-carotene reduces time to metamorphosis in a critically endangered frog, independent of growth effects. Supplementing captive frogs with dietary β-carotene could assist with amphibian conservation breeding programs globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…Similarly, β‐carotene has had positive effects on growth and development in tadpoles of the Booroolong frog ( Ranoidea booroolongensis ), but only when an intermediate dose of the supplement is provided (Keogh et al ., 2018). On the other hand, tadpoles of the Corroboree frog ( Pseudophryne corroboree ) have been shown to develop faster when supplemented with β‐carotene, but only at a high dosage (McInerney, Silla & Byrne, 2019). Regardless of dose, lutein had no detectable effects on development in this species (McInerney et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, β‐carotene has had positive effects on growth and development in tadpoles of the Booroolong frog ( Ranoidea booroolongensis ), but only when an intermediate dose of the supplement is provided (Keogh et al ., 2018). On the other hand, tadpoles of the Corroboree frog ( Pseudophryne corroboree ) have been shown to develop faster when supplemented with β‐carotene, but only at a high dosage (McInerney, Silla & Byrne, 2019). Regardless of dose, lutein had no detectable effects on development in this species (McInerney et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tadpoles of the Corroboree frog ( Pseudophryne corroboree ) have been shown to develop faster when supplemented with β‐carotene, but only at a high dosage (McInerney, Silla & Byrne, 2019). Regardless of dose, lutein had no detectable effects on development in this species (McInerney et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One group of dietary nutrients known to affect yellow/orange coloration are carotenoids (Brenes-Soto et al 2017). Dietary carotenoids are present in captive corroboree diets and recent experimental work has shown that P. corroboree possesses mechanisms needed to sequester and utilize dietary carotenoids (Umbers et al 2016;McInerney et al 2019). Moreover, enhanced carotenoid intake has been shown to alter skin coloration from a yellow to more orange coloration (Umbers et al 2016).…”
Section: Effect Of Colormentioning
confidence: 99%
“…Most carotenoids can effectively receive electrons, theoretically allowing them to quench and reduce the concentration of reactive oxygen species (ROS) in muscle tissue during periods of strenuous activity, improving physiological performance and endurance (Svennson & Wong, 2011;Koch & Hill, 2018). Indeed, dietary supplementation with carotenoids has been shown to positively influence various energetically costly physiological and behavioral traits, including growth and development (Keogh et al, 2018;McInerney et al, 2019) mating displays and ornamentation (Hill et al, 2002;Arnold et al, 2010) and predator escape response (Silla et al, 2016). Thus, there is reason to think that carotenoids might also positively affect other energetically demanding behavioral traits, such as exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the scarcity of studies, as well as variation in types of carotenoids used across studies, further work is required to determine how carotenoids influence exploratory behavior. Furthermore, a growing body of evidence suggests that the effects of carotenoids may be highly dose dependent, and also vary depending on the physiological and behavioral traits examined (Keogh et al, 2018;McInerney et al, 2019;McInerney et al, 2020). Thus, in order to significantly advance our understanding of the effect of dietary carotenoids on exploration behavior, additional studies investigating dose responses are required.…”
Section: Introductionmentioning
confidence: 99%